2019
DOI: 10.1155/2019/5813147
|View full text |Cite
|
Sign up to set email alerts
|

Adult Cardiac Stem Cell Aging: A Reversible Stochastic Phenomenon?

Abstract: Aging is by far the dominant risk factor for the development of cardiovascular diseases, whose prevalence dramatically increases with increasing age reaching epidemic proportions. In the elderly, pathologic cellular and molecular changes in cardiac tissue homeostasis and response to injury result in progressive deteriorations in the structure and function of the heart. Although the phenotypes of cardiac aging have been the subject of intense study, the recent discovery that cardiac homeostasis during mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 219 publications
0
34
0
Order By: Relevance
“…Since 2003, it has been reproducibly shown that the adult heart harbors a population of CSCs that participate in cardiac responses to injury and physiological CM turnover during the lifespan [11,13,14,19,21,[54][55][56][57][58]. CSCs cells are clonogenic, self-renewing and multipotent, giving rise to a minimum of three different cardiogenic cell lineages (myocytes, smooth muscle and endothelial cells) both in vitro and in vivo and exhibit significant cardiac tissue regenerative capacity [18][19][20][21].…”
Section: Resident Cardiac Stem/progenitor Cells In Adult Myocardial Tmentioning
confidence: 99%
“…Since 2003, it has been reproducibly shown that the adult heart harbors a population of CSCs that participate in cardiac responses to injury and physiological CM turnover during the lifespan [11,13,14,19,21,[54][55][56][57][58]. CSCs cells are clonogenic, self-renewing and multipotent, giving rise to a minimum of three different cardiogenic cell lineages (myocytes, smooth muscle and endothelial cells) both in vitro and in vivo and exhibit significant cardiac tissue regenerative capacity [18][19][20][21].…”
Section: Resident Cardiac Stem/progenitor Cells In Adult Myocardial Tmentioning
confidence: 99%
“…CSCs exposed to statins show a pronounced commitment to myogenesis through a balanced and very robust upregulation of myogenic transcription factors and ensuing expression of sarcomeric genes. These effects raise the potential for a similar effect on senescent CSCs in aging, where both CSC growth and differentiation are significantly impaired [3,[51][52][53][54][55]. The effects of acute exposure to statins both in vitro and in vivo remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that a few sub populations exist, e.g., the Lin−c-kitpos CSCs (c-kit positive cells and negative for blood/endothelial markers) that differ from other CSC and are able to differentiate not only to cardiomyocytes but also to endothelial cells and smooth muscle cells [ 12 ]. However, it has been shown that their cardio regenerative capability may be affected by different factors such as a diploid level of c-kit receptors [ 13 ], and that while they retain their cardiomyogenic potential (as can be expected from a cardiac stem cells), manipulation methods to fully use their cardio regenerative properties both in vivo and in vitro are still lacking [ 14 ].…”
Section: Introductionmentioning
confidence: 99%